2015
DOI: 10.1101/015404
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

FGF/MAPK signaling sets the switching threshold of a bistable circuit controlling cell fate decisions in ES cells

Abstract: Intracellular transcriptional regulators and extracellular signaling pathways together regulate the allocation of cell fates during development, but how their molecular activities are integrated to establish the correct proportions of cells with particular fates is not known. Here we study this question in the context of the decision between the epiblast (Epi) and the primitive endoderm (PrE) fate that occurs in the mammalian preimplantation embryo. Using an embryonic stem (ES) cell model, we discover two succ… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
21
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(23 citation statements)
references
References 38 publications
2
21
0
Order By: Relevance
“…Addition of MEKi alone, however, led to a specific reduction of the XEN-like subpopulation ( Supplementary Fig. 7c-e), in agreement with previous results 26,27 . This effect was unlikely due to interference with RA signaling since increasing RA concentration did not reverse the effect ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 81%
See 4 more Smart Citations
“…Addition of MEKi alone, however, led to a specific reduction of the XEN-like subpopulation ( Supplementary Fig. 7c-e), in agreement with previous results 26,27 . This effect was unlikely due to interference with RA signaling since increasing RA concentration did not reverse the effect ( Supplementary Fig.…”
Section: Resultssupporting
confidence: 81%
“…The epiblast lineage then further develops to neuroectoderm-like cells by 96 h. A recently published study by Klein et al used single-cell RNA-seq to characterize mESC differentiation by LIF withdrawal 41 and also found a small XEN-like subpopulation. That and other studies 42,27 show that XEN-like cells occur more generally in in vitro differentiation of mESCs and are not an idiosyncratic artefact of exposure to RA. We also found that mESCs grown in 2i/L (but not in serum and LIF) efficiently generate XEN cells under RA exposure ( Supplementary Fig.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations